Microtubule affinity regulating kinase 4 promoted activation of the NLRP3 inflammasome-mediated pyroptosis in periodontitis - Lulu Wang; Wenchen Pu; Chun Wang; Lang Lei; Houxuan Li (Journal of Oral Microbiology, 2022)
Background Microtubule dynamics plays a crucial role in the spatial arrangement of cell organelles and activation of the NLRP3 inflammasome. Purpose This study aimed to explore whether microtubule affinity regulating kinase 4 (MARK4) can be a therapeutic target of periodontitis by affecting microtubule dynamics and NLRP3 inflammasome-mediated pyroptosis in macrophages. Materials and Methods The NLRP3 inflammasome-related genes and MARK4 were measured in the healthy and inflamed human gingival tissues. Bone marrow-derived macrophages (BMDMs) were infected with Porphyromonas gingivalis, while the MARK4 inhibitors (OTSSP167 and Compound 50) and small interference RNA were utilized to restrain MARK4. Apoptosis-associated speck-like protein (ASC) speck was detected by confocal, and levels of interleukin-1β (IL-1β), as well as IL-18, were assessed by ELISA. Results Increased staining and transcription of MARK4, NLRP3, ASC, and Caspase-1 were observed in the inflamed gingiva. P. gingivalis infection promoted MARK4 expression and the NLRP3 inflammasome in BMDMs. Inhibition of MARK4 decreased LDH release, IL-1β and IL-18 production, ASC speck formation, and the pyroptosis-related genes transcription. Furthermore, MARK4 inhibition reduced microtubule polymerization and acetylation in P. gingivalis-infected BMDMs. Conclusions MARK4 promoted NLRP3 inflammasome activation and pyroptosis in P. gingivalis-infected BMDMs by affecting microtubule dynamics. MARK4 inhibition might be a potential target in regulating the NLRP3 inflammasome during periodontitis progress.